ELEMENTS OF POETRY THROUGH ROMANTIC PERSPECTIVE IN A NOVEL â€œLELAKI HARIMAUâ€ BY EKA KURNIAWAN - Natia Nur Aropah (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2022)
Literary works cannot be separated from the activity of thinking, imagining or observing sensitivity the author and his environment. This means that literary works are the result of an author's expressive feeling with full strength of heart, intuition and imagination. It's the same as the romantic criticism which prioritizes aspects of the heart, intuition and soul in expressing the natural context in literary work. This research aims to examine that how element of poetry through romantic perspective play a role in expressing the natural context in the novel Lelaki Harimau by Eka Kurniawan. This novel is beautifully conveyed by Eka about the beauty of nature until the reader feels it for real. For the element of poetry in this research thorough romantic perspective is nature was often presented as a work of art itself, constructed by a divine imagination, in emblematic language, and a nature full of wildness, irrational reason. Common life situation or rural life unite with the nature is a mature life landscape and a natural life according to Romantic perspective. However the next element of poetry is colouring imagination, something that is considered ordinary must be brought into our minds to be an unusual aspect. Making objects that we generally know are displayed uncommon. And the last element is prophetic intelligence how great the author is in processing text with the power of his words in a text that feels real, carried the reader into the soul and carried away by the atmosphere.Keywords: Romanticism; element of poetry ; nature